Bortezomib followed by autologous stem cell transplantation in a patient with rheumatoid arthritis: A case report and review of the literature. Issue 52 (December 2016) - Liu, Junru; Li, Juan; Chen, Meilan; Kuang, Lifen
Abstract: Rationale and Patients concerns: Despite the introduction of varied disease-modifying antirheumatic drugs and biological agents, a substantial proportion of patients remain untreatable. We report a 56-year-old Chinese female patient with a case of refractory rheumatoid arthritis (RA) complicated with multiple myeloma (MM) who was treated successfully with Bortezomib followed by autologous stem cell transplantation (ASCT). Diagnosis and Interventions: We report a 56-year-old Chinese female patient who was diagnosed as RA complicating with MM. She received 4 cycles of Bortezomib-based chemotherapy followed by ASCT. The response of her RA and MM were evaluated after every cycle of Bortezomib-based chemotherapy. Interventions and Outcomes: After the first Bortezomib-based chemotherapy cycle, this patient's symptoms were significantly alleviated and thereafter the RA activity continued to improve. After the 4 courses of Bortezomib-based chemotherapy, the C-reactive protein was <0.5 mg/dL and the disease activity score 28-erythrocyte sedimentation rate was 2.0. No hematological or nonhematological side effects were observed during the treatment of Bortezomib. Lessons: Bortezomib might be a new safe and promising drug for refractory RA patients.